Longitudinal Pressure Ulcer Rates After Adoption of Culture Change in Veterans Health Administration Nursing Homes. Issue 1 (19th January 2016) - Hartmann, Christine W.; Shwartz, Michael; Zhao, Shibei; Palmer, Jennifer A.; Berlowitz, Dan R.
Abstract : Objectives: To examine facility‐level pressure ulcer (PrU) development rates and variations in these rates after a system‐wide adoption of culture change in Veterans Health Administration (VHA) nursing homes. Design: Four‐year retrospective longitudinal design. Setting: VHA facilities (N = 109) representing 132 nursing homes known as community living centers (CLCs). Participants: VHA nursing home residents. Measurements: PrUs were identified using fiscal year (FY) 2008–11 Minimum Data Set (MDS) data. PrU development was defined as a Stage 2 or larger PrU on an MDS assessment with no PrU on the previous assessment. A risk adjustment model was developed using 105, 274 MDS observations to predict the likelihood of PrUs (c‐statistic = 0.72). A Bayesian hierarchical model that adjusted for differences in the precision of PrU rates from different‐size facilities was used to calculate smoothed risk‐adjusted (SRA) rates for each facility. The statistical significance of the trend over the 4 years was determined by examining the 95% interval estimate for the slope. Results: Over the 4‐year period, the beginning of which coincided with the VHA's system‐wide adoption of culture change as a performance measure, median SRA facility PrU development rates were fairly consistent at approximately 4%. The range in SRA rates declined over the years, from a 14.8‐percentage point spread to 10.1‐percentage point spread. Some facilities had significantly improving SRA rates (e.g., declined steadily from 5.5% to 3.9%) and some had significantly worsening SRA rates (e.g., increased steadily from 5.1% to 7.9%). Seven sites had significantly improving rates ( P  < .001) that were below the median across all 4 years. Conclusion: A system‐wide culture change implementation did not affect CLC PrU development rates, but there was significant variation in facility rates, and some facilities had sustained high performance.